A New Use for an Old Drug: Carmofur Attenuates Lipopolysaccharide (LPS)-Induced Acute Lung Injury via Inhibition of FAAH and NAAA Activities - Wu, Kangni; Xiu, Yanghui; Zhou, Pan; Qiu, Yan; Li, Yuhang (Frontiers in Pharmacology, 2019)
Acute lung injury (ALI), characterized by a severe inflammatory process, is a complex syndrome that can lead to multisystem organ failure. Fatty acid amide hydrolase (FAAH) and N-acylethanolamine acid amidase (NAAA) are two potential therapeutic targets for inflammation-related diseases. Herein, we identified carmofur, a 5-fluorouracil-releasing drug and clinically used as a chemotherapeutic agent, as a dual FAAH and NAAA inhibitor. In Raw264.7 macrophages, carmofur effectively reduced the mRNA expression of pro-inflammatory factors, including IL-1β, IL-6, iNOS, and TNF-α, and down-regulated signaling proteins of the nuclear transcription factor κB (NF-κB) pathway. Furthermore, carmofur significantly ameliorated the inflammatory responses and promoted resolution of pulmonary injury in lipopolysaccharide (LPS)-induced ALI mice. The pharmacological effects of carmofur were partially blocked by peroxisome proliferator-activated receptor-α (PPARα) antagonist MK886 and cannabinoid receptor 2 (CB2) antagonist SR144528, indicating that carmofur attenuated LPS-induced ALI in a PPARα- and CB2-dependent mechanism. Our study suggested that carmofur might be a novel therapeutic agent for ALI, and drug repurposing may provide us effective therapeutic strategies for ALI.